2017
DOI: 10.4172/2476-2059.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbiological Quality of Raw Milk from Farmers and Dairy Producers in Six Districts of Djibouti

Abstract: Objectives: The present study was carried out to evaluate the microbial quality of raw milk taken at different sampling points from farmers in Ali Sabieh, Arta, Dikhil, Djibouti, Obock and Tadjourah districts of Djibouti. Methods:Two hundred samples of milk extracted from goats, cows and camels were collected and analyzed for the presence and enumeration of microorganisms using standard methods. Total bacterial counts exceeded the national standard in 56% of collected samples and Tadjourah district had higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In India, Chaturvedi and Shukla [38] reported that 51.61% of raw milk samples were found to be highly contaminated with Clostridium species due to unhygienic milking practice. Mohamed et al [39] observed no germs of S. aureus and spore of Clostridium spp. in all cow and goat milk samples at Djibouti.…”
Section: Effects Of Hpp On Microbiological Propertiesmentioning
confidence: 99%
“…In India, Chaturvedi and Shukla [38] reported that 51.61% of raw milk samples were found to be highly contaminated with Clostridium species due to unhygienic milking practice. Mohamed et al [39] observed no germs of S. aureus and spore of Clostridium spp. in all cow and goat milk samples at Djibouti.…”
Section: Effects Of Hpp On Microbiological Propertiesmentioning
confidence: 99%
“…In a recent study was observed that in small dairy farms, the quality of raw milk was affected by inadequate transport conditions (De-Silva et al, 2016). Additionally, high counts in the number of coliform microorganisms and moderate variations in milk temperature were reported (Fatouma-Mohamed-Latif et al, 2017). Another factor with negative effect is the season.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the current millenia, Brucella abortus, Coxiella burnetti, and Mycobacterium bovis causing brucellosis, Q fever, and bovine tuberculosis, respectively, were the main pathogens of concern in milk (Singhal et al, 2020). Contrary to the reality in most developed countries, where the incidence of the aforementioned bacteria in milk products has been relatively curtailed, these pathogenic bacteria still remain a major problem to safety of milk products across SSA (Donkor, Aning, & Quaye, 2010;Fatouma-Mohamed et al, 2017;Hiwot, Savoinni, Donata, Gabriella, & Martino, 2016;Silaigwana, Green, & Ndip, 2012;Swai & Schoonman, 2011 contaminate milk products across SSA (Table 2). These notorious pathogens notably E. coli O157:H7, L. monocytogenes, and Salmonella rank among the leading cause of foodborne diseases worldwide (Newell et al, 2010).…”
Section: Milkborne Bacterial Pathogensmentioning
confidence: 99%